2BC Non-Structural Protein of Enterovirus A71 Interacts with SNARE Proteins to Trigger Autolysosome Formation - Lai, J.K.F.; Sam, I.C.; Verlhac, P.; Baguet, J.; Eskelinen, E.L.; Faure, M.; Chan, Y.F. (MDPI, 2017)
Viruses have evolved unique strategies to evade or subvert autophagy machinery. Enterovirus A71 (EV-A71) induces autophagy during infection in vitro and in vivo. In this study, we report that EV-A71 triggers autolysosome formation during infection in human rhabdomyosarcoma (RD) cells to facilitate its replication. Blocking autophagosome-lysosome fusion with chloroquine inhibited virus RNA replication, resulting in lower viral titres, viral RNA copies and viral proteins. Overexpression of the non-structural protein 2BC of EV-A71 induced autolysosome formation. Yeast 2-hybrid and co-affinity purification assays showed that 2BC physically and specifically interacted with a N-ethylmaleimide-sensitive factor attachment receptor (SNARE) protein, syntaxin-17 (STX17). Co-immunoprecipitation assay further showed that 2BC binds to SNARE proteins, STX17 and synaptosome associated protein 29 (SNAP29). Transient knockdown of STX17, SNAP29, and microtubule-associated protein 1 light chain 3B (LC3B), crucial proteins in the fusion between autophagosomes and lysosomes) as well as the lysosomal-associated membrane protein 1 (LAMP1) impaired production of infectious EV-A71 in RD cells. Collectively, these results demonstrate that the generation of autolysosomes triggered by the 2BC non-structural protein is important for EV-A71 replication, revealing a potential molecular pathway targeted by the virus to exploit autophagy. This study opens the possibility for the development of novel antivirals that specifically target 2BC to inhibit formation of autolysosomes during EV-A71 infection.